Frameless Patient Tracking With Adhesive Optical Skin Markers for Augmented Reality Surgical Navigation in Spine Surgery. Issue 22 (15th November 2020) - Burström, Gustav; Nachabe, Rami; Homan, Robert; Hoppenbrouwers, Jurgen; Holthuizen, Ronald; Persson, Oscar; Edström, Erik; Elmi-Terander, Adrian
Abstract : Study Design: Observational study. Objective: The aim of this study was to evaluate the accuracy of a new frameless reference marker system for patient tracking by analyzing the effect of vertebral position within the surgical field. Summary of Background Data: Most modern navigation systems for spine surgery rely on a dynamic reference frame attached to a vertebra for tracking the patient. This solution has the drawback of being bulky and obstructing the surgical field, while requiring that the dynamic reference frame is moved between vertebras to maintain accuracy. Methods: An augmented reality surgical navigation (ARSN) system with intraoperative cone beam computed tomography (CBCT) capability was installed in a hybrid operating room. The ARSN system used input from four video cameras for tracking adhesive skin markers placed around the surgical field. The frameless reference marker system was evaluated first in four human cadavers, and then in 20 patients undergoing navigated spine surgery. In each CBCT, the impact of vertebral position in the surgical field on technical accuracy was analyzed. The technical accuracy of the inserted pedicle devices was determined by measuring the distance between the planned position and the placed pedicle device, at the bone entry point. Results: The overall mean technical accuracy was 1.65 ± 1.24 mm at the bone entry point (n = 366). There was no statistically significant difference in technical accuracy between levels within CBCTs ( P ≥ 0.12 for all comparisons). Linear regressions showed that null- to negligible parts of the effect on technical accuracy could be explained by the number of absolute levels away from the index vertebrae ( r 2 ⩽ 0.007 for all, β ⩽ 0.071 for all). Conclusion: The frameless reference marker system based on adhesive skin markers is unobtrusive and affords the ARSN system a high accuracy throughout the navigated surgical field, independent of vertebral position. Level of Evidence: 3 Abstract : In contrast to conventional spinal navigation systems, a novel frameless reference marker system for spinal navigation maintained a high accuracy throughout the surgical field, independent of the vertebral position in relation to the index vertebra. The overall technical accuracy was 1.65 ± 1.24 mm.